2011
DOI: 10.4103/2229-5119.83948
|View full text |Cite
|
Sign up to set email alerts
|

Glycosides fraction extracted from fruit pulp of Cucumis metuliferus E. Meyer has antihyperglycemic effect in rats with alloxan-induced diabetes

Abstract: Introduction:The antihyperglycemic property of glycosides extracted from Cucumis metuliferus was tested in albino rats with alloxan-induced diabetes. Materials and Methods: Five groups of rats labeled A to E, each group containing fi ve rats, were made diabetic by intraperitoneal (i.p.) administration of alloxan 150 mg/kg. The groups A to E were and treated with normal saline, 25 mg/kg extract, 50 mg/kg extract, 100 mg/kg extract, and chlorpropamide 100 mg/kg, respectively. The blood glucose concentrations (BG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Diabetes mellitus is a metabolic disorder in which a combination of hereditary and environmental results in abnormally high blood sugar levels (hyperglycemia). The abnormal high blood sugar level is due to defects in either insulin secretion or insulin action in the body [ 1 ]. Diabetes mellitus is characterized by hyperglycemia, lipoprotein abnormalities, raised basal metabolic rate, defect in enzymes, and high oxidative stress which induced damage to pancreatic beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disorder in which a combination of hereditary and environmental results in abnormally high blood sugar levels (hyperglycemia). The abnormal high blood sugar level is due to defects in either insulin secretion or insulin action in the body [ 1 ]. Diabetes mellitus is characterized by hyperglycemia, lipoprotein abnormalities, raised basal metabolic rate, defect in enzymes, and high oxidative stress which induced damage to pancreatic beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…According to our research, there are not any recent in vitro studies on this subject concerning the kiwano specie. Only Jimam et al [46] and Gotep [47] have demonstrated that glycosides extracted from the fruit pulp of kiwano possess a dosedependent antihyperglycemic activity against alloxan-induced diabetes mellitus in albino rats. Jimam et al [46] reported that orally administration, via the intraperitoneal route, of 1000 and 1500 mg kg À1 of the kiwano fruit extract produced a significant ( p <0.05) decrease in the blood glucose concentration of hyperglycemic rats compared to that produced by tolbutamide (the standard reference drug).…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%
“…The percentage reductions in blood glucose concentration after 24 h were 56.0%, 51.1%, 65.2%, and 68.8% for rats treated with 100 mg Kg À1 chlorpropamide (the standard drug solution), 25 mg Kg À1 extract, 50 mg Kg À1 extract, and 100 mg Kg À1 kiwano extract, respectively. Jimam et al [46] and Gotep [47] proved that the glycosides from C. metuliferus possess antihyperglycemic activity in albino rats with alloxan-induced diabetes, demonstrating that kiwano study is a promising area of research into plant-based antidiabetic agents. However, the mechanism of action, as well as the structure and toxicity of the bioactive components of kiwano, are yet unknown and must be also further investigated to become a viable option in medicine [45].…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%
“…Recent studies have shown that the fruit of Cucumis. metuliferus increases the values of blood parameters as haemoglobin, red blood cell counts and white blood cells, cell volume and in vitro shows antibacterial activity against Salmonella gallinarum [14]; shows antiviral activity, as demonstrated by the regression of symptoms in chickens, turkeys and other birds affected by avian pseudosepta due to the genus Avulavirus [15]; the extract of the pulp has a protective and anti-ulcer action on the mucous membranes of mice with a dose-dependent effect [16]; increases male fertility [17]; the glycosides extracted from the pulp possess antihyperglycemic dose-dependent activity in allosane-induced diabetes mellitus in rats [18,19], the organic extracts of Kiwano leaves also present antimalarial activity with a suppression value of 98.55% compared to 100% of the chloroquine, suggesting the presence of active phytochemical compounds [20].…”
Section: Pharmacological Activitymentioning
confidence: 99%